The Prevalence of Potential Drug-Drug-Gene Interactions: A Descriptive Study Using Swiss Claims Data - Wittwer NL; Meier CR; Huber CA; Moser JD; Meyer zu Schwabedissen HE; Allemann SS; Schneider C (Pharmacogenomics and Personalized Medicine)
Nina L Wittwer,1,2 Christoph R Meier,1– 3 Carola A Huber,4 Julie D Moser,1 Henriette E Meyer zu Schwabedissen,5 Samuel S Allemann,6,* Cornelia Schneider1,2,* 1Basel Pharmacoepidemiology Unit, Division of Clinical Pharmacy and Epidemiology, Department of Pharmaceutical Sciences, University of Basel, Basel, Switzerland; 2Hospital Pharmacy, University Hospital Basel, Basel, Switzerland; 3Boston Collaborative Drug Surveillance Program, Lexington, MA, USA; 4Department of Health Sciences, Helsana Group, Zürich, Switzerland; 5Biopharmacy, Department of Pharmaceutical Sciences, University of Basel, Basel, Switzerland; 6Pharmaceutical Care, Department of Pharmaceutical Sciences, University of Basel, Basel, Switzerland*These authors contributed equally to this workCorrespondence: Samuel S Allemann, Pharmaceutical Care Research Group, University of Basel Department of Pharmaceutical Sciences Klingelbergstrasse 504056 Basel, Switzerland, Email s.allemann@unibas.chPurpose: We aimed to determine the prevalence of interactions between PGx drugs metabolized by CYP2C9, CYP2C19, and CYP2D6 and drugs that act as inhibitors or inducers of those enzymes in the Swiss population.Patients and Methods: We defined concomitant use of PGx drugs and inhibitors/inducers as instances where a claim of a PGx drug and a claim of an inducer or inhibitor concerning the same enzyme were made within a specified temporal window, either ± 5 days or ± 30 days. We assessed concomitant drug use between 2017 and 2021, using claims data from a Swiss insurance company (Helsana).Results: Out of 894,748 individuals continuously insured, between 17.4% (± 5-days window) and 24.8% (± 30-days window) were exposed to potentially interacting drug pairs, with 1.5% to 2.2% being exposed to potentially strong interacting drug pairs. Individuals exposed to potentially interacting drugs were more frequently female, older and took a greater number of drugs than the general population. The majority of potential interactions were associated with CYP2D6 or CYP2C19.Conclusion: In light of the high prevalence of the simultaneous use of PGx drugs with inhibitor and inducer drugs, it is imperative to consider non-genetic factors, such as drug-induced phenoconversions, when interpreting PGx test results.Keywords: drug-drug interaction, drug-drug-gene interaction, phenoconversion